Independence of Judges in Deciding Criminal Cases Perspective on the Principle of Legality - Maskanah, Ummi (Ann Publisher, 2024)
Judges' independence in resolving criminal cases ensures justice and legal certainty inside the legal system from the standpoint of the legality principle. Independence from unlawful interference, autonomy in interpreting the law, and independence from internal and external pressure are all included. Judges must be strengthened to enhance the concept of judges' independence as much as possible. The legality concept can be seen in judges' suitable and effective resolution of criminal cases, which results in justice and legal certainty. To gain a complete picture of judges' independence in making decisions about criminal cases from the standpoint of legality principles, this study employed a normative juridical approach method, utilizing secondary data gathered through literature research with primary, secondary, and tertiary legal materials. The data was then analyzed using qualitative juridical methods. As a foundation for guaranteeing justice in the legal system, the study's findings indicated that judges' independence in resolving criminal cases from a legal standpoint is crucial. The legality principle, which highlights the idea that there can be no crime without law, must serve as the foundation for judges' independence in making decisions on criminal matters. In order to protect the defendant and uphold justice and legal certainty, the judge is not allowed to overstep or break any of the legal restrictions placed to stop abuse of authority. Beyond imposing penalties that fall short of the legal minimum, judges are also constrained by the idea of legality. Researchers contend that material legality, which emphasizes community-felt justice through ideas like restorative justice, should be added to the definition of legality. More research is still needed on this transition.